Distribution and Seasonal Abundance of Macro Benthos of Gangavali Estuary, Uttar Kannada, West Coast of India - V.N. Nayak, Shirodkar S.R* and (Journal of Ecobiotechnology, 2010)
<span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">Distribution and seasonal abundance of Gangavali estuary was studied for one year from September 2007 to August 2008. The diversity, abundance and biomass of macro-benthos were observed selecting four stations along the Gangavali estuary and eleven benthic organisms were encountered in the present study. Polycheates were observed at all four stations with maximum faunal distribution. The diversity of macro benthos was at maximum numbers towards lower reaches of the estuary. The benthic faunal components exhibit bimodal pattern of distribution with monsoon as a period of minimum density and post-monsoon and early pre-mansion with maximum density.